Assessing safety culture and stress-related disorders among chemical laboratory workers in Sri Lanka: A cross-sectional study - Sanduni Wasana Panangala Liyanage; S.D.N.A.M. Amila Madhushanka Weerasinghe; Seung Cheol Hong (International Journal of Occupational Safety and Health, 2025)
Introduction: This cross-sectional study investigates the relationship between safety culture and stress-related disorders (SRDs) among chemical laboratory workers in Sri Lanka's academic, industry, and government sectors. Understanding the impact of safety culture on mental health is essential for developing effective interventions.